A Study of Non-Euclidean s-Topology. (5th July 2012) - Agrawal, Gunjan; Shrivastava, Sampada
Abstract : The present paper focuses on the characterization of compact sets of Minkowski space with a non-Euclidean s -topology which is defined in terms of Lorentz metric. As an application of this study, it is proved that the 2-dimensional Minkowski space with s -topology is not simply connected. Also, it is obtained that the n -dimensional Minkowski space with s -topology is separable, first countable, path-connected, nonregular, nonmetrizable, nonsecond countable, noncompact, and non-Lindelöf.